REPRESENTATION THE PHRASE “LOVE YOURSELF” IN THE LYRICS “EPIPHANY” BY JIN BTS - Daniella, Aviel (Serat: Journal of Literary & Cultural Studies, 2025)
This study investigates how Jin from BTS's song Epiphany uses the term "Love Yourself" in its lyrics. Insecurity and mental health, which are common among today's young, are directly related to the idea of self-love. BTS actively encourages self-love as a strategy for overcoming fear through their songs and activities like "LOVE MYSELF," which they co-created with UNICEF. Through an analysis of the song's lyrics and its implied and explicit meanings, this article investigates how Epiphany delivers this message. To guarantee an accurate interpretation, the study examines various English translations of the lyrics using a qualitative methodology. According to the results, Epiphany illustrates the process of self-discovery and stresses the value of self-love in spite of one's flaws and emotional difficulties. The protagonist of the song first dedicates his life to serving others, but he eventually comes to see his own value and the importance of loving himself. This study adds to the conversation of music as a tool for raising awareness of mental health issues and emphasizes how BTS builds uplifting stories about accepting oneself. The study emphasizes how young listeners can benefit from music as a powerful tool for reducing uneasiness and promoting self-compassion.